Insights into the Interactions among Roots, Rhizosphere, and Rhizobacteria for Improving Plant Growth and Tolerance to Abiotic Stresses: A Review - Khan, Naeem; Ali, Shahid; Shahid, Muhammad Adnan; Mustafa, Adnan; Sayyed, R. Z.; Curá, José Alfredo (Cells (Basel, Switzerland), 2021)
Abiotic stresses, such as drought, salinity, heavy metals, variations in temperature, and ultraviolet (UV) radiation, are antagonistic to plant growth and development, resulting in an overall decrease in plant yield. These stresses have direct effects on the rhizosphere, thus severely affect the root growth, and thereby affecting the overall plant growth, health, and productivity. However, the growth-promoting rhizobacteria that colonize the rhizosphere/endorhizosphere protect the roots from the adverse effects of abiotic stress and facilitate plant growth by various direct and indirect mechanisms. In the rhizosphere, plants are constantly interacting with thousands of these microorganisms, yet it is not very clear when and how these complex root, rhizosphere, and rhizobacteria interactions occur under abiotic stresses. Therefore, the present review attempts to focus on root–rhizosphere and rhizobacterial interactions under stresses, how roots respond to these interactions, and the role of rhizobacteria under these stresses. Further, the review focuses on the underlying mechanisms employed by rhizobacteria for improving root architecture and plant tolerance to abiotic stresses.